2008
DOI: 10.1016/j.yhbeh.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol interacts with the cholinergic system to affect verbal memory in postmenopausal women: Evidence for the critical period hypothesis

Abstract: Estradiol has been shown to interact with the cholinergic system to affect cognition in postmenopausal women. This study further investigated the interaction of estradiol and cholinergic system functioning on verbal memory and attention in two groups of healthy younger (ages 50-62) and older (ages 70-80) postmenopausal women. Twenty-two postmenopausal women were randomly and blindly placed on 1 mg of 17-beta estradiol orally for one month then 2 mg for two months or matching placebo pills after which they part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 64 publications
11
87
2
1
Order By: Relevance
“…Whether there are interactions with the cholinergic (and/or other neurotransmitter) systems that change with aging and can mitigate steroids' cognitive effects is of interest [5,19]. It is likely that some of the effects are due to actions of 3α,5α-THP.…”
Section: Rotarodmentioning
confidence: 99%
“…Whether there are interactions with the cholinergic (and/or other neurotransmitter) systems that change with aging and can mitigate steroids' cognitive effects is of interest [5,19]. It is likely that some of the effects are due to actions of 3α,5α-THP.…”
Section: Rotarodmentioning
confidence: 99%
“…Estradiol reduced the effects of nicotinic and muscarinic acetylcholine antagonism on tests of attention and verbal learning and memory (Dumas et al, 2008;Dumas et al, 2006). TMX has estrogen-like effects on the central, cholinergic system, supporting the possibility of estrogen-like enhancements on cognition (McMillan et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…Studies in our (Dumas et al, 2008;Dumas et al, 2006;Dumas et al, 2012) and other labs revealed that estrogen acts in part through the cholinergic system to benefit cognition (as reviewed by Gibbs (2010)). Estradiol reduced the effects of nicotinic and muscarinic acetylcholine antagonism on tests of attention and verbal learning and memory (Dumas et al, 2008;Dumas et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Neuroprotection in Perimenopausal Women http://dx.doi.org/10.5772/intechopen.74330 135 and macrophages to 17β-E2 [90], and this fact may be an explanation of some studies showing better results with ET on memory recall in women aged around 70 and 20 years postmenopausal, if women have not demonstrated memory impairment [91].…”
Section: Sex Hormones In Neurodegenerative Processes and Diseases 132mentioning
confidence: 99%